MATHEMATICS THROUGH LANGUAGE AND LANGUAGE THROUGH MATHEMATICS: CONDENSATION TRANSCRIPTION AS A POINT OF SYMBIOSIS - Janice Hill (Фізико-математична освіта)
This paper explores the idea of condensation transcription—which is defined as the reduction of lengthy collections of lexical elements or mathematical descriptions into short forms—as the point where mathematics and language learning cross-influence one another notably. To elaborate, condensation transcription is defined as the linguistic ability and procedure that permits the reconstruction and compacting of larger lexical sets into more manageable forms while maintaining the basic meanings of those sets. Such a phenomenon occurs when mathematical concepts are rewritten from page-long descriptions to figures and numerical entities, and when literary passages are compressed into their main ideas.